S124 The effectiveness of "in-clinic" smoking cessation support in the setting of secondary care respiratory outpatient services. (15th November 2016) - Valero-Sanchez, I; Agrawal, S; Brij, S; Evans, RA; Greening, NJ; Perry, M; Toms, N; Wiggins, E; Williams, J; Steiner, MC
Abstract : Introduction and aims: Although two thirds of smokers wish to quit, referral, uptake and engagement with smoking cessation (SC) services are frequently poor. In Leicester, uptake of smoking cessation referred from secondary care is approximately 20% with successful quit rate at four weeks of 10%. Provision of immediate support through smoking cessation specialist advice provided at the point of clinical assessment in outpatients might enhance referral uptake and quit rates. We assessed the value of this "in-clinic" approach in specialist respiratory outpatient clinics in two secondary care centres. Methods: Provision of immediate smoking cessation advice was implemented in two outpatient clinic services providing specialist care for patients with complex, chronic obstructive pulmonary disease (COPD); an Acute General Hospital (Peterborough City Hospital, PCH) and a Tertiary Care Hospital (Glenfield Hospital, GH). All current smokers were referred to an on-site smoking cessation specialist advisor by the physician, or clinic nurse, as part of their outpatient review on the same day of their clinic visit. In the Glenfield service SC was provided by a smoking cessation specialist, using a harm reduction approach with a guided patient-led tailored programme and the possibility of direct supply treatment at the initial assessment. In the PCH service, SC using psychosocial and/or pharmacological therapy was undertaken by a dedicated smoking cessation officer Follow-up visits and telephone calls were arranged separately by the smoking service and data including demographics, treatment uptake and quit rates after 4 weeks were analysed. Results: A population of 122 smokers with a diagnosis of COPD were assessed for in-clinic SC over a period of twelve months in both centres. Demographic details of both cohorts, outcomes of both SC strategies including treatment uptake and quit rates are disclosed in Table 1 . Conclusions: Providing "in-clinic", expert smoking cessation advice results in favourable referral uptake and four week quit rates when compared with locally available data from paper based referral routes. Reinforcing physician delivered smoking cessation advice through immediate provision of proactive cessation support may be an effective means to enhance quit rates in secondary care.